Plasma and energetic particle observations in Jupiter's deep tail near the magnetopause. Issue 8 (22nd August 2014) - Kollmann, P.; Ebert, R. W.; Haggerty, D. K.; Bagenal, F.; Elliott, H. A.; McComas, D. J.; Hill, M. E.; Paranicas, C.; Delamere, P. A.; Brown, L.; McNutt, R. L.
Abstract Jupiter's nightside magnetosphere stretches out into an extensive magnetotail. New Horizons observed continuously over 1 AU down Jupiter's tail, far more than any other spacecraft. Previously, Voyager 2 showed signatures of the tail as far as 4 AU distance from Jupiter. We combine data from New Horizons' charged particle instruments: Solar Wind Around Pluto, measuring plasma ions (21–7800 eV/Q), and Pluto Energetic Particle Spectrometer Science Investigation, measuring energetic ions and electrons (0.03–1.6 MeV). The magnetosheath is clearly distinguished from the magnetotail, owing to more plasma ions. They are often separated by a boundary layer with intermediate properties at plasma energies but resemblance to the magnetotail at higher energies. Compared to the tail, the sheath contains on average more energetic protons and helium ions (potential solar wind origin) and fewer energetic electrons, oxygen, and sulfur ions (latter two of magnetospheric origin). The difference between tail and sheath for energetic ions and electrons is less pronounced than for plasma ions, which may result from particle exchange. We have ruled out that this is due to gyroradius. Energetic ion count rate enhancements with velocity dispersion cross between tail, boundary layer, and sheath. This indicates occasional magnetic connections since the enhancements are interpreted as particles following magnetic flux tubes. The deep tail magnetic field is therefore not entirely separated from the solar wind. Brief magnetic connection will mostly allow the fastest particles to cross, in agreement with the observations. Most dispersed enhancements include sulfur ions consistent with an origin near Jupiter's X line. We found one event of mostly protons, indicating an origin at larger distances.